Financing the Frontline in Papua New Guinea : An Analytical Review of Provincial Administrations' Rural Health Expenditure 2006-2012 - Cairns, Alan; Hou, Xiaohui (World Bank, Washington, DC, 2016)
Financing the Frontline updates the expenditure analysis carried out in Below the Glass Floor (2013) and tests whether the spending patterns emerging in 2009 and 2010 in Papua New Guinea have been sustained or improved in 2011 and 2012. The review also supports a better understanding of the issues that confront frontline service delivery — such as the ambiguity of roles and responsibilities in some rural health functions — and proposes next steps. Concurrently, the National Department of Health performance information on facilities (from the National Health Information System) has been reviewed. The integration of the expenditure analysis, the NHIS performance information and the findings from the Promoting Effective Public Expenditure facility surveys will provide a rich source of information to help sharpen understanding and shape solutions.